Synthesis Of Natural Rubber Palygorskite Composite Via Combine Latex Compounding And Melt Mixing - Nor, Nor Aina Mohd (2017)
The fabrication of nanocomposite based on palygorskite (PAL) and natural rubber (NR) was prepared by a combination of melt mixing and latex compounding methods. The objectives of this study was divided into four which are the mixing time variation of PAL, the sonication time of PAL, the different filler loading of PAL and the effect of surface treatment using silylation method of PAL. The obtained results from previous series was related to the next series which the characterization of NR/PAL nanocomposites, the mechanical and physical properties, and the morphology testing of NR/PAL nanocomposites were conducted to test the samples. In the first series, 60 minutes of PAL mixing time (PAL60) produced a better cure characteristics, good mechanical and physical properties, and an increasing in glass transition temperature, Tg which it indicates the better rubber-filler interaction than other samples. For the second series, 30 minutes of PAL sonication time (S30) displayed an improving in cure characteristics, good mechanical and physical properties with producing good dispersion of PAL in the matrix by supporting with intercalated structure as shown by XRD data. The shifting of Tg towards higher temperature indicated a restriction in chain mobility. Next, in the third series of study, 4 phr of PAL loading (PAL4) demonstrated good results in mechanical properties and morphological testing. The good results of PAL4 was also supported from XRD patterns which is PAL 4 shows the intercalated structure and it represents a well dispersion of PAL in the matrix. Finally, in the last series, the PAL is treated with two type of silane; 3-(Trimethoxysily) propyl methacrylate-silane (METHA) and Bis [3- (tri ethoxy silyl) propyl] Tetrasulfide-silane (TESPT). The characterisation of PAL with and without silane treatment was determined using Fourier Transform Infra-Red (FTIR) spectroscopy analysis. The present of hydroxyl and carbonyl groups in the PAL after underwent silane surface treatment assisting in producing well dispersion of PAL in the matrix. NR/PAL-TESPT showed better mechanical properties, good dispersion of PAL with thicker tear line and rougher surface and a broad peak of XRD patterns than NR/PAL-METHA.